Perencanaan Strategi Sistem Informasi Penjualan Menggunakan Pendekatan Togaf Adm (Studi Kasus : Three Sister’s House Of Beauty) - Cecep Kurnia Sastradipraja; Dudih Gustian; Sarah Sifa Antadipura (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2019)
Three Sister’s House Of Beauty is one of the several business located at karangtengah cibadak sukabumi. This Business offers all things about skincare, makeup and fashion for youngest to the oldest especially for a man. In the process business activity, Three Sister's has implement strategic planning, but in this prospect the planning has a missed targeted so that it cannot be realized properly, the problems regarding data collection process of sold product and ordering data for customers sometimes just written, input into Ms.Word and Ms.Excel. In odd moment, Three Sister’s share and promotion product on social media, the community of beauty have every rules if want post on group. So that, Three Sister's House of Beauty must planning of ISand IT strategies to be good business proces in future. The conclusion, strategic planning for implementing Enterprise Architecture is one of the best solutions for supports a business or organization. So with this, the author conducts research with the study of the Togaf ADM to support Sales Information Systems that are integrated, right on target, and support business processes in Three Sisters' House of Beauty.